Inhibition of Excision of Oxidatively Generated Hydantoin DNA Lesions by NEIL1 by the Competitive Binding of the Nucleotide Excision Repair Factor XPC-RAD23B - Kolbanovskiy, Marina (Biochemistry, 2020)
The interplay between nucleotide excision repair (NER) and base excision repair (BER) of non-bulky, oxidatively generated DNA lesion, has long been a subject of significant interest. The hydantoin oxidation products of 8-oxoguanine, spiroiminodihydantoin (Sp) and 5-guanidinohydantoin (Gh), are substrates of both BER and NER in HeLa cell extracts and human cells [Shafirovich et al. (2019) Chem. Res. Toxicol. 32, 753–761]. The primary factor that recognizes DNA lesions is the DNA damage-sensing factor XPC-RAD23B (XPC), while the glycosylase NEIL1 is known to remove Gh and Sp lesions from double-stranded DNA. It is shown here that in aqueous solutions containing nanomolar concentrations of proteins, XPC and NEIL1 compete for binding to 147-mer oligonucleotide duplexes that contain single Gh or Sp lesions under conditions of [protein] >> [DNA] concentrations, thus inhibiting the rate of BER catalysed by NEIL1. The non-covalently bound NEIL1 molecules can be displaced by XPC at concentration ratios R = [XPC]/[NEIL1] > 0.2, while full displacement of NEIL1 is observed at R ≥ 0.5. In the absence of XPC and under single turnover conditions, only the burst phase is observable. However, upon progressively increasing the XPC concentration, the amplitude of the burst phase decreases gradually, and a slower time-dependent phase of incision product formation manifests itself with rate constants of 3.0×10(−3) (Gh) and 0.90×10(−3) s(−1) (Sp). These slow kinetics are attributed to the dissociation of XPC-DNA complexes that allow for the rebinding of NEIL1 to the temporarily exposed Gh or Sp lesions, and the incisions observed under these steady-state conditions.